THE CONCRETE STRUCTURES DESIGN WITH RATIONAL GRAIN STRUCTURE COMPONENTS - Netesa, M. I.; Palanchuk, D. V. (Science and Transport Progress, 2008)
The problems of utilization of the secondary products of industry in the concretes and increase of efficiency of the use of cement providing the rational composition of components are considered.